Metal–organic frameworks and their derivatives for metal-ion (Li, Na, K and Zn) hybrid capacitors. Issue 41 (29th September 2022) - Zhan, Feiyang; Wang, Huayu; He, Qingqing; Xu, Weili; Chen, Jun; Ren, Xuehua; Wang, Haoyu; Liu, Shude; Han, Minsu; Yamauchi, Yusuke; Chen, Lingyun
Abstract : This review summarizes the progress of metal–organic frameworks and their derivatives as advanced multifunctional platforms for metal-ion hybrid capacitors. Abstract : Metal-ion hybrid capacitors (MIHCs) hold particular promise for next-generation energy storage technologies, which bridge the gap between the high energy density of conventional batteries and the high power density and long lifespan of supercapacitors (SCs). However, the achieved electrochemical performance of available MIHCs is still far from practical requirements. This is primarily attributed to the mismatch in capacity and reaction kinetics between the cathode and anode. In this regard, metal–organic frameworks (MOFs) and their derivatives offer great opportunities for high-performance MIHCs due to their high specific surface area, high porosity, topological diversity, and designable functional sites. In this review, instead of simply enumerating, we critically summarize the recent progress of MOFs and their derivatives in MIHCs (Li, Na, K, and Zn), while emphasizing the relationship between the structure/composition and electrochemical performance. In addition, existing issues and some representative design strategies are highlighted to inspire breaking through existing limitations. Finally, a brief conclusion and outlook are presented, along with current challenges and future opportunities for MOFs and their derivatives in MIHCs.